Pyridostigmine Induced Prolonged Asystole in a Patient with Myasthenia Gravis Successfully Treated with Hyoscyamine - Mohammad Saud Khan; Abhinav Tiwari; Zubair Khan; Himani Sharma; Mohammad Taleb; Jeffrey Hammersley (Case Reports in Cardiology)
Reversible acetylcholinesterase inhibitors are used as first-line treatment for myasthenia gravis. They improve symptoms by increasing concentration of acetylcholine at the neuromuscular junction and stimulating nicotinic receptors. Serious bradyarrhythmias can occur from muscarinic stimulation in heart, which in rare cases may progress to asystole. These patients can initially be managed with hyoscyamine, a muscarinic antagonist. Persistence of bradyarrhythmias even after hyoscyamine treatment may warrant pacemaker placement. We present a case of 65-year-old female patient who presented with diplopia, dysphagia, and muscle weakness who was diagnosed with myasthenia gravis. She developed significant sinoatrial node block with prolonged asystole after starting treatment with pyridostigmine which was successfully treated with hyoscyamine, thus avoiding pacemaker placement.